Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1177/0310057x1304100317
|View full text |Cite
|
Sign up to set email alerts
|

Donation after Cardiac Death in Non-Survivable Burns

Abstract: Major burns have previously been considered a contraindication to solid organ donation. We present two cases of successful organ donation and transplantation, after Maastricht category III cardiac death in adult patients with non-survivable burns injury. The implications of the outcome of these cases are that major burns should not be considered a contraindication to organ donation, and that cardiac death provides opportunity for patients with non-survivable burns to contribute to the pool of potential organ d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Widdicombe et al reported two successful cases of organ donation and transplantation after Maastricht category III cardiac death, in adult patients with non-survivable burn injuries. Good outcomes were achieved for both cases [2]. DCD in burn injured patients raises medical challenges related to the potential risks of splanchnic ischemic injury following burn shock, together with a high risk of bacterial contamination and sepsis [26].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Widdicombe et al reported two successful cases of organ donation and transplantation after Maastricht category III cardiac death, in adult patients with non-survivable burn injuries. Good outcomes were achieved for both cases [2]. DCD in burn injured patients raises medical challenges related to the potential risks of splanchnic ischemic injury following burn shock, together with a high risk of bacterial contamination and sepsis [26].…”
Section: Discussionmentioning
confidence: 99%
“…In the past, the risk of ischemic organ injury, caused by burn shocks, was the rationale for considering major burns as a contraindication to organ donation. With acute intensive care progresses and innovations, this contraindication has lost absoluteness [2, 6]. As a matter of fact, the reported organ survival rates for major burned donors reached 86% [5] and the long-term outcomes are good too [4] (3).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations